A review of the genus Dexia Meigen in the Palearctic and Oriental Regions (Diptera: Tachinidae) - Zhang, Chun-Tian; Shima, Hiroshi; Chen, Xiao-Lin (Zootaxa, 2010)
The Palearctic and Oriental species of the genus Dexia Meigen are revised. Thirty-one described species are recognized as valid, viz. D. atripes (Malloch), D. basifera Walker, D. bivittata Townsend, D. caldwelli Curran, D. divergens Walker, D. extendens Walker, D. flavida (Townsend), D. flavipes Coquillett, D. fraseri (Malloch), D. fulvifera Röder, D. fusiformis Walker, D. gilva Mesnil, D. hainanensis Zhang, D. lepida Wiedemann, D. longipennis (Townsend), D. longipes (Townsend), D. luzonensis (Townsend), D. major (Malloch), D. maritima Kolomiets, D. montana (Baranov), D. monticola Malloch, D. rustica (Fabricius), D. seticincta Mesnil, D. subnuda (Malloch), Dexia sumatrensis (Townsend, 1926), status nov. (originally described as Eomyoceropsis sumatrensis Townsend, 1926 and here removed from synonymy with D. fulvifera), D. vacua (Fallén), D. velutina (Mesnil), D. ventralis Aldrich, D. vicina (Mesnil), D. violovitshi Kolomiets and D. vittata (Baranov). Five species are described as new to science: D. alticola Zhang et Shima, sp. nov., D. chaoi Zhang et Shima, sp. nov., D. chinensis Zhang et Chen, sp. nov., D. kurahashii Zhang et Shima, sp. nov., and D. tenuiforceps Zhang et Shima, sp. nov. Some species are newly recorded from Japan and Southeast and South Asian countries. A key to 36 species of Dexia is given and 96 diagnostic figures of the male terminalia are included.